Nutritional Assessment in Patients with Early-Onset Autosomal Dominant Alzheimer's Disease Due to PSEN1- E280A Genetic Variant: A Cross-Sectional Study (2021)
ABSTRACT: Background: Weight loss and malnutrition are frequent findings in late-onset and sporadic presentations of Alzheimer's Disease (AD). However, less is known about nutritional status in Early-Onset Autosomal Dominant AD (EO-ADAD). Objective: To analyze the association between nutritional status and other clinical and sociodemographic characteristics in individuals with a genetic form of EO-ADAD. Design settings and participants: Cross-sectional study with 75 non-institutionalized participants from a cohort of Autosomal Dominant AD (13 with mild cognitive impairment and 61 with dementia, ages from 38 to 67 years) underwent a structured clinical assessment with emphasis on nutritional status. Measurements: Primary outcome was nutritional status and it was measured using the Mini Nutritional Assessment (MNA). Patients were categorized according to MNA total score, as undernourished (MNA ≤23.5) and well-nourished (MNA ≥ 24). Sociodemographic and clinical variables identified as potential predictors or confounders of nutritional status were also collected. Results: Undernourishment by MNA was present in 57.3% of the sample. Forty-two percent of participants had abnormal BMI values considered lower than 18.5 or higher than 24.9 kg/m2. Total BMI values were similar in well and undernourished patients (median 24.2 IQR 3.59 and median 23.9 IQR 4.42, respectively, p=0.476). When comparing well and undernourished groups, we found statistically significant differences for variables: severity of dementia (p=0.034), frailty (p=0.001), multimorbidity (p=0.035) and, polymedication (p=0.045). Neither adjusted logistic regression nor the Poisson regression showed that any clinical or sociodemographic variables explained undernourishment. Conclusions: Undernourishment was a frequent finding in our sample of EO-ADAD, especially in later stages of the disease. Patients with polymedication, multimorbidity, frailty and severe dementia show differences in their nutritional status with a tendency to be more frequently undernourished. Further studies with larger sample sizes are needed to establish this association.